Haem is crucial for medium-dependent metronidazole resistance in clinical isolates of Clostridioides difficile. (20th April 2021) - Boekhoud, Ilse M; Sidorov, Igor; Nooij, Sam; Harmanus, Céline; Bos-Sanders, Ingrid M J G; Viprey, Virginie; Spittal, William; Clark, Emma; Davies, Kerrie; Freeman, Jane; Kuijper, Ed J; Smits, Wiep Klaas; et al.
Abstract: Background: Until recently, metronidazole was the first-line treatment for Clostridioides difficile infection and it is still commonly used. Though resistance has been reported due to the plasmid pCD-METRO, this does not explain all cases. Objectives: To identify factors that contribute to plasmid-independent metronidazole resistance of C. difficile. Methods: Here, we investigate resistance to metronidazole in a collection of clinical isolates of C. difficile using a combination of antimicrobial susceptibility testing on different solid agar media and WGS of selected isolates. Results: We find that nearly all isolates demonstrate a haem-dependent increase in the MIC of metronidazole, which in some cases leads to isolates qualifying as resistant (MIC >2 mg/L). Moreover, we find an SNP in the haem-responsive gene hsmA, which defines a metronidazole-resistant lineage of PCR ribotype 010/MLST ST15 isolates that also includes pCD-METRO-containing strains. Conclusions: Our data demonstrate that haem is crucial for medium-dependent metronidazole resistance in C. difficile .